MicroRNA and Cancer: Tiny Molecules with Major Implications - VandenBoom II, Timothy G.; Li, Yiwei; Philip, Philip A.; Sarkar, Fazlul H. (Current Genomics, 2008)
Cancer is currently a major public health problem and, as such, emerging research is making significant progress in identifying major players in its biology. One recent topic of interest involves microRNAs (miRNAs) which are small, non-coding RNA molecules that inhibit gene expression post-transcriptionally. They accomplish this by binding to the 3' untranslated region (3'UTR) of target messengerRNA (mRNA), resulting in either their degradation or inhibition of translation, depending on the degree of complementary base pairing. They are transcribed by RNA polymerase II and are formed into mature miRNAs via two steps, each catalyzed by a different ribonuclease III (RNaseIII). Cross-species comparisons demonstrate that miRNAs are evolutionarily conserved and play important roles in a wide array of normal biological processes. Importantly, aberrant miRNA expression is correlated with human disease, especially in the development of cancer. Recent research has identified targets and functions of miRNAs, illustrating that some are oncogenic in nature while others show tumor suppressor activity. The miRNAs have also been characterized as having high potential in the clinical arena and, as such, have been a target for exploitation toward cancer therapy. Not only has it been shown that miRNA expression profiles may prove useful as diagnostic and prognostic markers in cancer, various miRNA-based therapies show promise as well. It is anticipated that further research will elucidate the benefits of using miRNAs as clinical agents in the battle against cancer and other chronic diseases.
Keywords: biogenesis